The development of the methodology of a passive health surveillance system through a sentinel network of general/family practitioners in South Africa - De Villiers, Pierre Johannes Truter (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D.) -- University of Stellenbosch, 1999.